FACTORS AFFECTING THE WELFARE OF FISHERMEN'S HOUSEHOLDS IN BENGKULU PROVINCE - Oktapiani, Melanda; Cahyadinata, Indra; Khairani, Lathifah; Istriningsih (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Bengkulu Province has great marine potential and a long coastline, but the welfare of fishermen is still an issue that needs attention. This study aims to analyze the level of welfare and the factors that influence the welfare of fisher households in Bengkulu Province. The research location is in Bengkulu Province. In this study, the sample consisted of 200 purposively selected fisher households. Data were collected through secondary sources from the March 2023 National Socio-Economic Survey (Susenas) and related agencies. For data analysis, quantitative descriptive method and binary logistic regression were used to see the factors affecting the welfare of fisher households. The results show that the highest level of welfare is in Mukomuko District with a percentage of 93.75%. Factors that are proven to have a probability effect on the welfare of fisher households include the number of family dependents and the status of Non-Cash Food Assistance (BPNT) recipients. In contrast, variables such as age, years of education, boat ownership, as well as participation in assistance programs such as Kartu Keluarga Sejahtera (KKS) and Program Keluarga Harapan (PKH), are unlikely to have a significant effect on the welfare of fisher households in Bengkulu Province. These findings indicate that the government's role in raising awareness of the importance of limiting the number of family members can be done through socialization on family planning. The government needs to focus support through the BPNT assistance program on fisher households with more than four family members to improve their welfare.